The p16-Specific Reactivation and Inhibition of Cell Migration Through Demethylation of CpG Islands by Engineered Transcription Factors - Zhang, Baozhen (Mary Ann Liebert, Inc., 2012)
Methylation of CpG islands inactivates transcription of tumor suppressor genes including p16 (CDKN2A). Inhibitors of DNA methylation and histone deacylation are recognized as useful cancer therapeutic chemicals through reactivation of the expression of methylated genes. However, these inhibitors are not target gene–specific, so that they lead to serious side effects as regular cytotoxic chemotherapy agents. To explore the feasibility of methylated gene-specific reactivation by artificial transcription factors, we engineered a set of Sp1-like seven-finger zinc-finger proteins (7ZFPs) targeted to a 21-bp sequence of the p16 promoter and found that these 7ZFPs could bind specifically to the target p16 promoter probe. Then the p16-specific artificial transcription factors (p16ATFs) were made from these 7ZFPs and the transcription activator VP64. Results showed that transient transfection of some p16ATFs selectively up-regulated the endogenous p16 expression in the p16-active 293T cells. Moreover, the transient transfection of the representative p16ATF-6I specifically reactivated p16 expression in the p16-methylated H1299 and AGS cells pretreated with a nontoxic amount of 5’-aza-deoxycytidine (20 and 80 nM, respectively). In addition, stable transfection of the p16ATF induced demethylation of p16 CpG island and trimethylation of histone H3K4, and inhibited recruitment of DNA methyltransferase 1 and trimethylation of H3K9 and H3K27 in the p16 promoter in H1299 cells without 5’-aza-deoxycytidine pretreatment. Notably, inhibition of cell migration and invasion was observed in these p16-reactivated cells induced by transient and stable p16ATF transfection. These results demonstrate that p16ATF not only specifically reactivates p16 expression through demethylation of CpG islands, but also restores methylated p16 function.